Measuring optimal psychological states: Proposal of two brief versions to measure flow and clutch in athletes - Sánchez Vara, Alejandro; Chamorro, José L.; Moreno Castellanos, Ruben; Alcaraz, Saul (Frontiers in Psychology, 2023)
Background: The study of sports experiences with high levels of performance has led to the observation of two psychological states categorized as optimal, denominated flow and clutch. The objective of this study is to design and validate two brief scales version to measure flow and clutch. Method: Following the MIMO (Maximum Information, Minimum Discomfort) protocol, three studies are carried out: In Study 1, we developed the short versions of the questionnaires based on theory-driven and data-driven criteria; in Study 2, we used quantitative criteria to validate the short versions; and in Study 3, we checked the final version of each scale to observe their statistical validity and their relation to other variables. Results: the new short flow scale is made up of seven items, while the clutch scale is made up of five items. Throughout the three studies, evidence is provided of the internal consistency, invariance of the measurement models and content internal validity, related to the responding process and in relation to other variables. Conclusions: This study provides two short versions to evaluate flow and clutch, which will help to continue advancing in the study of optimal psychological states in sport.